PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) INSPIRATIF PENDEKATAN TaRL BERBASIS PjBL MELALUI PEMBELAJARAN LITERASI SAINS MATERI VIRUS - Ospa Pea Yuanita Meishanti; Nur Afifah Rif'atul Fitri (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2022)
One of the problems faced by education in Indonesia today is the weakness of the learning process, where students are forced to memorize information, remember and hoard various information with a lack of understanding of the context of what they remember or learn and relate to everyday life. So this study develops an Inspirational learning tool based on PjBL based TaRL approach through learning scientific literacy on virus material with the aim of knowing the feasibility of learning tools and materials from the development of Learning Implementation Plans (RPP) which can then be applied in the school with the media used including STEM-based e-modules, STEM-based e-LKS Screencast and implementation of STEM-based interactive notebook biology on virus material, using the ADDIE development model and getting the results of the feasibility of learning designs with an average value of 91.66% and implementation in the learning process with a percentage of 100% very good. So it can be concluded that the product can be developed and implemented in MAN 10 Jombang schools.. KEYWORDS: RPP, Inspirational, TaRL, PjBL